Analisis Faktor-Faktor yang Mempengaruhi Kepuasan Kerja Pegawai Polsek Bayan Polres Purworejo - Damar Damar; Dewi Shanti Nugrahani; Anna Probowati (STIE Rajawali Purworejo, 2025)
This study focuses on the identification and resolution of Factors Affecting Employee Job Satisfaction (Salary, Working Conditions, Co-workers) of Bayan Police, Purworejo Police. The researcher distributed questionnaires to 24 employees of Bayan Police, Purworejo Police. As respondents in this study using the Likert scale formula as a sampling technique. The data analysis technique in this study used 3 variables, namely salary, working conditions and co-workers. The results of the study showed that respondents agreed that when viewed from the salary variable, it stated that Bayan Police employees, Purworejo Police agreed with the salary according to rank and position. The working conditions variable had a positive and significant effect on job satisfaction of Bayan Police employees, Purworejo Police, which was proven by respondents agreeing that when viewed from the working conditions variable, it stated that Bayan Police employees, Purworejo Police agreed with safe working conditions, free from danger and clean. Respondents were neutral that when viewed from the co- workers variable, it stated that Bayan Police employees, Purworejo Police were neutral, which means they have an attitude of impartiality between one member and another, willing to help me when facing difficulties.